Ella's wish - Eicher, Jerry S (Eugene, Or. : Harvest House Publishers, 2011)
"Ella Yoder has moved into her dream house. In the stillness of the great house, Ella ponders her options. How is she to survive on her own? How will she ever forget Aden? What is to become of her? Two would-be suitors soon make their intentions known, but Ella is unsure of her own feelings. As she agrees to take care of Preacher Stutzman's three motherless girls, Ella's heart is touched by their love for her. Could their affection be the answer to Ella's quest? Can God speak through the love of a child? Readers of Amish fiction will fall in love themselves with Ella Yoder and hope with her that she finds the love and happiness she seeks" -- Cover verso
Keywords: Amish -- Fiction; Loss (Psychology) -- Fiction; Motherless families -- Fiction